Molecular Mechanisms of Cardiac Injury Associated With Myocardial SARS-CoV-2 Infection - Liu, Xianfang; Lou, Longquan; Zhou, Lei (Frontiers in Cardiovascular Medicine, 2022)
Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread around the world. The development of cardiac injury is a common condition in patients with COVID-19, but the pathogenesis remains unclear. The RNA-Seq dataset (GSE150392) comparing expression profiling of mock human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) and SARS-CoV-2-infected hiPSC-CMs was obtained from Gene Expression Omnibus (GEO). We identified 1,554 differentially expressed genes (DEGs) based on GSE150392. Gene set enrichment analysis (GSEA), Gene ontology (GO) analysis, and Kyoto encyclopedia of genes and genomes (KEGG) pathway analysis showed that immune-inflammatory responses were activated by SARS-CoV-2, while muscle contraction, cellular respiration, and cell cycle of hiPSC-CMs were inhibited. A total of 15 hub genes were identified according to protein–protein interaction (PPI), among which 11 upregulated genes were mainly involved in cytokine activation related to the excessive inflammatory response. Moreover, we identified potential drugs based on these hub genes. In conclusion, SARS-CoV-2 infection of cardiomyocytes caused a strong defensive response, leading to excessive immune inflammation, cell hypoxia, functional contractility reduction, and apoptosis, ultimately resulting in myocardial injury.